China in Latin America: a follow-up on the development of the relations - Benjamin Creutzfeldt (Revista CS)
This paper examines five recently published books that deal with the issue of Chinese relations with the Americas between 2011 and 2014. The author shows that the books provide evidence of a steady China’s interest to Latin America and the Caribbean as well as a scale-up of diplomatic relationships and bilateral trade of commodities. At the same time, the ability of Latin American countries to provide an effective response to the Chinese attempts to use the bilateral arrangements in order to strengthen its participation in regional organizations is rather weak. This scenario allows a progressive and effective impact of China in the region to continue. The author argues that the way to better understand China’s relations with Latin America is via a multidisciplinary approach, which is not limited by the boundaries of one discipline or a research area only. Besides, it is important to take into account that -additionally to commerce and trade- China´s interaction within Latin America and the Caribbean also involves cultural, social, political, and global dimensions.